Stratigraphy of the western Nepal Lesser Himalaya: A synthesis - Upreti, B. N. (Journal of Nepal Geological Society, 1996)
The western Nepal Lesser Himalaya, lying between the Marsyangdi and Bheri Rivers, is generally free from crystalline nappes and exposes the sedimentary and metasedimentary rock sequences in a wide zone between the MBT and the MCT. Geologically, the area is complicated by the presence of a number of folds, thrusts and imbricate zones. Despite the complicated geology, excellent studies have been carried out in recent years on the stratigraphy of this region. However, individual work has been confined in areas separated by wide intervening parts that are not as well studied. Many researchers have proposed different stratigraphic nomenclatures in their respective study areas, and their stratigraphic subdivisions do not always correspond well with each other. Therefore, confusion and uncertainties have remained in the stratigraphic interpretation of the western Nepal Lesser Himalaya. An attempt has been made here to appraise and synthesize the work done so far to bring out a clearer picture of the problems and prospects in the stratigraphic investigations in western Nepal. For convenience, the stratigraphy of the Lesser Himalayan metasediments the younger group of fossiliferous sedimentary rocks and the Jajarkot Nappe are treated separately. An attempt has been made to extend the stratigraphic nomenclature of the Nawakot Complex of central Nepal established by Stocklin and Bhattarai (1977) and Stocklin (1980) to western Nepal. In spite of the type sections of these rocks in central Nepal and the rocks of western Nepal being separated by a large intervening area, there is a fair consistency in the stratigraphic sequence and rock assemblages in the two areas. The uniformity in the use of nomenclature of rock units will greatly help to build up a more systematic and reliable stratigraphy of Nepal Lesser Himalaya in the future. The low grade metamorphic and the sedimentary rocks of the Lesser Himalaya are divided into the older Nawakot Unit and the younger Tansen Unit. Only the Tansen Unit is fossiliferous. Whereas the Nawakot Unit is largely of Precambrian age, the Tansen Unit ranges in age from Permo-Carboniferous to Lower Tertiary. The Jajarkot Nappe, tectonically overlying the Lesser Himalayan metasediments, consists of medium grade metamorphic rocks such as garnet bearing schists, feldspathic schists and quartzites. These rocks are succeeded conformably by unmetamorphosed carbonate rocks of possibly Cambro Ordovician age and stratigraphically and tectonically comparable to the Phulchauki Group of the Kathmandu Nappe of central Nepal.